2011
DOI: 10.1186/1475-2875-10-386
|View full text |Cite
|
Sign up to set email alerts
|

Early and extensive CD55 loss from red blood cells supports a causal role in malarial anaemia

Abstract: BackgroundLevels of complement regulatory proteins (CrP) on the surface of red blood cells (RBC) decrease during severe malarial anaemia and as part of cell ageing process. It remains unclear whether CrP changes seen during malaria contribute to the development of anaemia, or result from an altered RBC age distribution due to suppressive effects of malaria on erythropoiesis.MethodsA cross sectional study was conducted in the north-east coast of Tanzania to investigate whether the changes in glycosylphosphatidy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Along these lines, several works have suggested that the erythrocyte complement regulatory proteins may play an important role in the pathogenesis of anemia, protecting nonparasitized RBCs from destruction. This hypothesis was tested by different researchers, who reported that changes in the expression patterns of some complement regulatory proteins such as complement receptor 1 (CR1) (118), decay-accelerating factor (CD55), and membrane inhibitor of reactive lysis (CD59) may render RBCs more susceptible to lysis, increasing their destruction and resulting in anemia (119)(120)(121)(122)(123)(124). Studies conducted in areas of P. falciparum endemicity have documented that higher levels of CR1 and CD55 are exhibited in RBCs from children with uncomplicated malaria or who are uninfected than in RBCs from those with severe anemia (119)(120)(121).…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…Along these lines, several works have suggested that the erythrocyte complement regulatory proteins may play an important role in the pathogenesis of anemia, protecting nonparasitized RBCs from destruction. This hypothesis was tested by different researchers, who reported that changes in the expression patterns of some complement regulatory proteins such as complement receptor 1 (CR1) (118), decay-accelerating factor (CD55), and membrane inhibitor of reactive lysis (CD59) may render RBCs more susceptible to lysis, increasing their destruction and resulting in anemia (119)(120)(121)(122)(123)(124). Studies conducted in areas of P. falciparum endemicity have documented that higher levels of CR1 and CD55 are exhibited in RBCs from children with uncomplicated malaria or who are uninfected than in RBCs from those with severe anemia (119)(120)(121).…”
Section: The Complement System and Malariamentioning
confidence: 99%
“…Nevertheless, mainly destruction of uninfected RBCs contributes to anemia, a process that is even more pronounced with P. vivax (Castro-Gomes et al 2014). RBC surface expression of complement regulatory proteins CR1 and CD55 is decreased, while C3b deposition is increased in P. falciparum-infected patients with SMA (Odhiambo et al 2008;Gwamaka et al 2011). Increased complement deposition could result from oxidative damage with subsequent band 3 receptor clustering induced by ROS release from phagocytes and/or by transfer of 4-HNE from iRBCs to uninfected RBCs in rosettes (Waitumbi et al 2000;Arese, Turrini and Schwarzer 2005;Odhiambo et al 2008;Uyoga et al 2012).…”
Section: Erythrocyte Destruction and Ineffective Erythropoiesismentioning
confidence: 99%
“…Changes in the cell surface markers associated with decreased viability and cells' stability occur during the aging both in vivo and in vitro [10][11][12][13]. Under the stressfull conditions, such as during the low-temperature cell storage, the changes in the surface markers may reflect the structural and functional membranes' rearrangements that could affect the cells' stability under the extreme conditions.…”
Section: Introductionmentioning
confidence: 99%